Safeguarding Maritime Critical Infrastructure: Indonesia’s Defense Diplomacy in the Indo-Pacific Security Architecture under the Joko Widodo Administration (2014–2024) - Nurjanah, Ita; Perwita, Anak Agung Banyu; Hendarwoto, Yermia (Asian Journal of Science, Technology, Engineering, and Art, 2025)
Maritime critical infrastructure (MCI)—comprising undersea data cables, energy pipelines, ports, and shipping lanes—is essential to sustaining global economic stability and digital connectivity. This is particularly critical in Southeast Asia, a region marked by dense maritime traffic and rising geopolitical tensions, including hybrid threats. As the largest archipelagic state in the region, Indonesia plays a pivotal role in safeguarding the security and resilience of these infrastructures. This study analyzes Indonesia’s defense diplomacy in protecting MCI within the broader Indo-Pacific security architecture during the administration of President Joko Widodo (2014–2024). Anchored in Barry Buzan’s Regional Security Complex Theory (RSCT), alongside the concepts of hedging and defense diplomacy, the research employs a qualitative descriptive method to examine Indonesia’s strategic positioning. Findings indicate that Indonesia’s approach emphasizes diplomatic engagement, regional institutional cooperation, and strategic autonomy—enabling it to enhance infrastructure resilience while preserving neutrality amid intensifying U.S.–China rivalry. Key enablers include the adoption of technological innovation, improved inter-agency coordination, and multilateral defense partnerships. The study concludes that Indonesia’s defense diplomacy not only contributes to national infrastructure protection but also reinforces the stability of the Indo-Pacific maritime order.